2000
DOI: 10.1038/74680
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide has anti-inflammatory effects involving the mitogen-activated protein kinase pathway

Abstract: The stress-inducible protein heme oxygenase-1 provides protection against oxidative stress. The anti-inflammatory properties of heme oxygenase-1 may serve as a basis for this cytoprotection. We demonstrate here that carbon monoxide, a by-product of heme catabolism by heme oxygenase, mediates potent anti-inflammatory effects. Both in vivo and in vitro, carbon monoxide at low concentrations differentially and selectively inhibited the expression of lipopolysaccharide-induced pro-inflammatory cytokines tumor necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

44
1,652
5
28

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,975 publications
(1,729 citation statements)
references
References 41 publications
44
1,652
5
28
Order By: Relevance
“…Consistent with this observation, neutrophil migration into the lung following an intratracheal challenge of LPS was attenuated when animals breathed air containing CO, but that was not attenuated in animals lacking p38 MAPK. 28,30 Inoue et al 34 have also demonstrated that neutrophil migration to the lung following LPS inhalation was markedly attenuated by pre-administration of an endogenous HO-1 inducer, hemin, or an Ad expressing HO-1 in mice, and further demonstrated that IL-10 overproduction by macrophages was essential for suppressed neutrophilic inflammation. Together, these data suggest that overexpression of HO-1 results in CO production, which modifies cytokine profiles within both inflammatory and respiratory epithelial cells, thus suppressing neutrophil migration into the lung in response to LPS.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Consistent with this observation, neutrophil migration into the lung following an intratracheal challenge of LPS was attenuated when animals breathed air containing CO, but that was not attenuated in animals lacking p38 MAPK. 28,30 Inoue et al 34 have also demonstrated that neutrophil migration to the lung following LPS inhalation was markedly attenuated by pre-administration of an endogenous HO-1 inducer, hemin, or an Ad expressing HO-1 in mice, and further demonstrated that IL-10 overproduction by macrophages was essential for suppressed neutrophilic inflammation. Together, these data suggest that overexpression of HO-1 results in CO production, which modifies cytokine profiles within both inflammatory and respiratory epithelial cells, thus suppressing neutrophil migration into the lung in response to LPS.…”
Section: Discussionmentioning
confidence: 98%
“…39,40 Similarly, CO, a by-product of HO-1-mediated heme degradation, has been shown in vitro to stimulate p38 MAPK, a molecule pivotal in the expression of various cytokines. [22][23][24]30 In this regard, Otterbein et al 28,30 have demonstrated that macrophages cultured in air containing CO showed an increase in IL-10, as well as a decrease in TNF-␣ and IL-1␤ production. Consistent with this observation, neutrophil migration into the lung following an intratracheal challenge of LPS was attenuated when animals breathed air containing CO, but that was not attenuated in animals lacking p38 MAPK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytoprotective properties of HO-1 have traditionally been attributed to the by-products of heme degradation, namely bilirubin and carbon monoxide (CO). Indeed, within a narrow therapeutic range, these catalytic by-products exert powerful antioxidant [15,31], antiinflammatory [32] and anti-apoptotic effects [33][34][35], leading to reduced infarct size [16,17,[36][37]. However, emerging evidence, suggests that HO-1 may also exert cytoprotective effects, independent of heme breakdown [38] by interacting with survival signaling pathways such as PI3K-Akt and p38.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 There are various forms of stress or tissue injury that can induce the expression of HO-1. Copious studies show that HO-1 and its products can maintain cellular homeostasis based on its anti-inflammatory, 11 antioxidative 12,13 and/or antiapoptotic 14,15 properties. In different models of transplantation, induction of HO-1 can protect grafts from I/R injury, [16][17][18] acute 14,19 and chronic rejection.…”
Section: Introductionmentioning
confidence: 99%